Simulation and prediction of BEV heat pumps system performance in cold climates - Nandi, Swaroop (My University, 2024)
The rapid evolution of the automotive sector toward electric vehicles is significantly propelled by the technological advancements in thermal management systems. Battery Electric Vehicles (BEVs) show a high sensitivity when it comes to temperature control. This study focuses on one such issue regarding thermal management systems of BEV. At lower temperature and high humidity levels, while using ambient heat for thermal comfort, the radiator while picking up heat acts as a condenser and because of high moister in the air there is a high probability of icing on the heat exchanger surface. This frost formed on the heat exchanger surface will hinder the heat transfer efficiency and thereby the thermal performance. Hence, predicting this frost formation on the heat is indispensable. This frost is a result of different physical parameters and thermodynamic properties that include, relative humidity, ambient temperature, coolant temperature, airflow rate and the interaction happening between these properties. Hence there is a need to understand these relations to predict the frost formation. This master thesis project centers on the prediction and simulation of BEV heat pump system performance in cold climates, particularly focusing on addressing the issue of frosting. Hence, there's a critical need for reliable methodology to simulate and predict its formation under varying conditions, enabling a deeper understanding of the correlation between environmental factors and performance parameters of heat exchanger. The methodology focuses on establishing a numerical correlation between different frost parameters. Developing mathematical models and employing the numerical correlations to accurately predict the onset of frost, sufficing this issue is key in advancing BEV heat pump systems. By closing the gap between theory and practical application, this thesis seeks to contribute to the development of a reliable and efficient BEV heat pump systems. This research also emphasizes on vital aspect of defrosting. Effective defrosting strategies are necessary for preserving vehicle thermal comfort and performance. The research follows a comprehensive approach, starting with a comprehensive literature review of the current state of research in the field. Lastly, the simulations & mathematical models will undergo rigorous experimental verification with an existing experiment on Volvo Cars Corporation radiators and establishes a possible numerical relation between frost parameters. Ultimately, the research aims to enhance the efficiency and reliability of BEV heat pump systems through simulations and analysis, particularly in cold climates, thereby contributing to the ongoing evolution of electric vehicle technology.
Keywords: Thermal management; Frosting; Defrosting; BEV heat pumps; GT-Suite